Proposed new strategy in CQI at course module level through students' feedbacks in UNITEN - Long C.Y.; Jern K.P. (Institute of Electrical and Electronics Engineers Inc., 2023)
Accreditation; Education; Engineering education; Continuous quality improvement; Course modules; Malaysia; new strategy; Quality education; Students